2013
DOI: 10.1037/a0031490
|View full text |Cite
|
Sign up to set email alerts
|

Face and object cognition across adult age.

Abstract: We investigated the specificity of face compared with object cognition from an individual differences and aging perspective by determining the amount of overlap between these abilities at the level of latent constructs across age. Confirmatory factor analytic models tested the specificity of speed and accuracy measures for face and object cognition (N = 448; 18 to 88 years). Accuracy measures were distinguishable and slightly dedifferentiated across age, which was not due to loss of visual acuity and contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…Hildebrandt et al (2011) observed no dedifferentiation of individual differences in the latent constructs of face cognition as compared to general cognitive functioning. This finding was further substantiated in a subsequent study comparing object and face processing, in which only a slight dedifferentiation was observed, which was not specific for faces but operated on a more general cognitive level (Hildebrandt et al, 2013). In the present study, the behavioral ORB was equivalent between groups, although overall memory was reduced in low performers.…”
Section: Discussionmentioning
confidence: 61%
“…Hildebrandt et al (2011) observed no dedifferentiation of individual differences in the latent constructs of face cognition as compared to general cognitive functioning. This finding was further substantiated in a subsequent study comparing object and face processing, in which only a slight dedifferentiation was observed, which was not specific for faces but operated on a more general cognitive level (Hildebrandt et al, 2013). In the present study, the behavioral ORB was equivalent between groups, although overall memory was reduced in low performers.…”
Section: Discussionmentioning
confidence: 61%
“…One study found a perfect correlation between the speed of face cognition and the speed of processing for emotional expressions, however the speed of face cognition factor correlated only moderately with object cognition speed [80]. More importantly, the other study showed that the speed measures of face cognition reflect the same ability as speed measures for objects [81]. The authors concluded that this ability captures the speed of processing complex visual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, in LSEMs weights are used to treat context variables as continuous variables instead of creating artificial categories. The statistical procedures for defining the bandwidth of the kernel function, calculating the weights for every focal point and rescaling of the weights have been described elsewhere (Hildebrandt, Sommer, Herzmann, & Wilhelm, 2010;Hildebrandt, Wilhelm, Herzmann, & Sommer, 2013;Hildebrandt et al, 2009;Hülür et al, 2011). Note that weighted models could not be calculated for focal points at the very edges of the distribution of the context variable because estimation for each focal point requires a sufficient number of cases below and above that focal point (symmetrical weighting).…”
Section: Statistical Analysesmentioning
confidence: 99%